Identify problems and special needs education of gifted students in social work educator - Демченко, О. П.; Цюх, Н. А. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2017)
The place in the structure of the diagnostic functions of social workers, peculiarities and problems of social and educational diagnosis of gifted children. The results of the study to identify social and psychological problems and disability gifted and talented students, the circle of children with symptoms of different types of talent that require social and educational work.